Animation: Friend or Foe in Today’s Classrooms? - Koch, Ronald J.; Edgar, Don W.; Wardlow, George W. (Journal of Agricultural Systems, Technology, and Management, 2012)
Classrooms hold a vast amount of knowledge for today’s students. Through the advancement of technological devices, both hardware and software, the arsenal of today’s teachers seems unlimited. Animation of intricate theories and processes has been touted to increase understanding of students (Larive, 2008; Wouters, Pass, & van Merriënboer, 2008; McGregor, 2002; Su, 2008) and this study engaged in analyzing the effects of animation in purposively selected classrooms through a counterbalance design. Theories of operation and carburetion were taught to the selected participates. Regarding cognitive achievement of the selected participants towards principles and theories tested, no significant differences were found between technology enhanced and traditional means of education. Further variables of study including gender, time of instruction, and tinkering self-efficacy were not found to have significant effects. This study concurs with previous research that technology enhanced teaching does not significantly affect cognitive achievement.